A pilot study of nimotuzumab combined with cisplatin and 5-FU in patients with advanced esophageal squamous cell carcinoma - Ling, Yang (Pioneer Bioscience Publishing Company, 2012)
OBJECTIVE: To observe the short-term effect and adverse reaction of Nimotuzumab in combination with chemotherapy on advanced esophageal squamous cell carcinoma (ESCC). METHOD: 19 patients were treated with the following protocol: Nimotuzumab 400mg/time/week in the 1(st) week, 200mg/time/week from the 2(nd) to 8(th) week, intravenous drip (IVD); Cisplatin 80 mg/m(2), IVD, 4 weeks a cycle and repeated again; 5-FU 750 mg/m(2), continuous 24-hours pump-in × 5 days, 4 weeks a cycle and repeated again. RESULT: 16 of all 19 patients can be evaluated. After treatment, RP is 42.1% (95% CI, 19.9-64.3%) and DCR is 68.4%; the main side effects include arrest of bone marrow, gastrointestinal reactions, asthenia, etc. CONCLUSION: Nimotuzumab in combination with cisplatin/5-FU regimens in patients with advanced ESCC is safe and effective, which deserves a further expanded sample research.